PENGARUH RESTATEMENT LAPORAN KEUANGAN TERHADAP KINERJA PASAR SETELAH IMPLEMENTASI IFRS - Deanita Sari; Puji Harto (Jurnal Akuntansi Universitas Muhammadiyah Kupang, 2019)
The purpose of this research is to find out if there is any impact of accounting restatement on market performance. The object of this study are non-finance which were listed in Indonesia stock exchange (IDX) from the year of 2012-2017. The datas used in this research are secondary data in the form of annual report and other datas associated with IDX-listed companies. The independent variables of this study accounting restatement. The dependent variables of this research is abnormal return. The control variables of this study indust, asset, leverage, IFRS, total akun and total restatement. Result of this study shows that accounting restatement significantly affects cumulative abnormal return. The result is similar to some previous studies.